Moral equality, war, and defence of the community : a critque and reconceptualisation of moral equality - Gercama, Atje (Irish School of Ecumenics, 2015)
This thesis focuses on Michael Walzer’s argument for the moral equality of soldiers and aims to reconceptualise moral equality. This concept explains why it is not a crime when soldiers kill each other during a war. In recent years, Walzers argument has been the subject of a number of critiques; most of these critiques focus on the fact that Walzer does not hold soldiers responsible for the justness of a war.
Keywords: Religions, Peace Studies & Theology, Ph.D.; Ph.D. Trinity College Dublin